В а, б повыделяем полные квадраты:
x^2-6x+4=(x^2-6x+9)-5=(x-3)^2-5
Вершина (3,-5)
-x^2-4x+1=-(x^2+4x+4)+5=-(x+2)^2+5
Вершина (-2,5)
в)
x0=-b/2a=-(-12)/(2*3)=2
y0=f(x0)=3*4-12*2+2=-10
Вершина (2,-10)
абсциссы вершины параболы вычисляется по формуле:
x₀ = -b / 2a
а)x₀ = 6 / 2 = 3
y₀ = 3² - 6 * 3 + 4 = 9 - 18 + 4 = -9 + 4 = -5
б)x₀ = -b / 2a = 4 / -2 = -2
y₀ = -(-2)² + 4 * 2 + 1 = -4 + 8 + 1 = 4 + 1 = 5
в)x₀ = -b / 2a = 12 / 6 = 2
y₀ = 3 * 2² - 12 * 2 + 2 = 12 - 24 + 2 = -12 + 2 = -10
В а, б повыделяем полные квадраты:
x^2-6x+4=(x^2-6x+9)-5=(x-3)^2-5
Вершина (3,-5)
-x^2-4x+1=-(x^2+4x+4)+5=-(x+2)^2+5
Вершина (-2,5)
в)
x0=-b/2a=-(-12)/(2*3)=2
y0=f(x0)=3*4-12*2+2=-10
Вершина (2,-10)
абсциссы вершины параболы вычисляется по формуле:
x₀ = -b / 2a
а)x₀ = 6 / 2 = 3
y₀ = 3² - 6 * 3 + 4 = 9 - 18 + 4 = -9 + 4 = -5
б)x₀ = -b / 2a = 4 / -2 = -2
y₀ = -(-2)² + 4 * 2 + 1 = -4 + 8 + 1 = 4 + 1 = 5
в)x₀ = -b / 2a = 12 / 6 = 2
y₀ = 3 * 2² - 12 * 2 + 2 = 12 - 24 + 2 = -12 + 2 = -10